Research progress on microbial community and maintenance technology of pit mud of strong-flavor Baijiu - WU Shukun, MU Minmin, YANG Lei (Zhongguo niangzao, 2024)
As one of the main sources of brewing microorganisms, pit mud plays an important role in the formation of strong-flavor (Nongxiangxing) Baijiu style, and the degradation of pit mud directly affect the production and quality of strong-flavor Baijiu. In this paper, the differences of community structure and functional application of pit mud microorganisms were comprehensively described, the causes and preventive measures of pit mud degradation were summarized, and the research and application of pit mud maintenance technology in recent years were summarized, in order to provide reference for the utilization of pit mud functional microorganisms and the application of pit mud maintenance technology.